2018
DOI: 10.1111/pde.13623
|View full text |Cite
|
Sign up to set email alerts
|

Unusual skin manifestations associated with parvovirus B19 primary infection in children

Abstract: Parvovirus B19 is a DNA virus of the Parvoviridae family. We present four children with unusual exanthems associated with parvovirus infection: a purpuric periflexural pattern, a purpuric vasculitic pattern, and a combination of the two.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 10 publications
0
4
0
5
Order By: Relevance
“…The authors concluded that B19 infection should be suspected in cases of polymorphic and purpuric or petechial exanthemas with fever and other systemic symptoms. Differential diagnoses include other classic exanthematic diseases but also meningococcemia, acute hemorrhagic edema, rickettsia infections, or infections with ß-hemolytic streptococci [62]. Mage et al [63] described four exanthema patterns associated with B19 infection according to morphology and distribution: reticular, vasculitis-like, periflexural, and acral.…”
Section: Parvovirus B19mentioning
confidence: 99%
See 2 more Smart Citations
“…The authors concluded that B19 infection should be suspected in cases of polymorphic and purpuric or petechial exanthemas with fever and other systemic symptoms. Differential diagnoses include other classic exanthematic diseases but also meningococcemia, acute hemorrhagic edema, rickettsia infections, or infections with ß-hemolytic streptococci [62]. Mage et al [63] described four exanthema patterns associated with B19 infection according to morphology and distribution: reticular, vasculitis-like, periflexural, and acral.…”
Section: Parvovirus B19mentioning
confidence: 99%
“…The authors concluded that B19 infection should be suspected in cases of polymorphic and purpuric or petechial exanthemas with fever and other systemic symptoms. Differential diagnoses include other classic exanthematic diseases but also meningococcemia, acute hemorrhagic edema, rickettsia infections, or infections with ß‐hemolytic streptococci [62].…”
Section: Parvovirus B19mentioning
confidence: 99%
See 1 more Smart Citation
“…Нерідко у пацієнтів спостерігається синдром папульозно пурпурових рукавичок та шкарпеток [41]. Існують численні повідо млення про незвичайні екзантеми у дітей, інфі кованих PVB19 [13,14]. У деяких дітей може бути скарлатино макуло папульозний висип на шкірі, із розташуванням у пахвових склад ках із відцентровим розширенням у напрямку грудної клітки та проксимальної частин рук.…”
Section: обговоренняunclassified
“…У більшості пацієнтів хвороба перебігає безсимптомно і викликає самообмежуючі неспецифічні симптоми, такі як висип, лихоманка, міалгії та артралгії у людей [31,51,65]. У фахових публікаціях повідомляється, що PVB19 інфекція у дітей асоціюється з низкою патологічних станів: васкуліт [55,66], нефрит [25,38,64], артеріїт [17], системний червоний вовчак [4,54], енце фаліт [25,43], хвороба Кавасакі [46], міокар дит [30,26,62], гепатит [27,33], артрит [17] та іншими [7,14,15,21,31,37,39,61]. Цей вірус викликає різноманітні гематологічні прояви: парціальну еритроцитичну аплазію [42,57,63], гемолітичну анемію [41], нейтропенію [28,32], ідіопатичну [2] та амегакаріоцитарну тромбо цитопенію [5], комбінацію нейтропенії та тромбоцитопенії [60], гемофагоцитарний лім фогістіоцитоз [26].…”
unclassified